Human osteoblasts within soft peptide hydrogels promote mineralisation in vitro. (2nd July 2014) - Castillo Diaz, Luis A; Saiani, Alberto; Gough, Julie E; Miller, Aline F
Biomaterials that provide three-dimensional support networks for the culture of cells are being developed for a wide range of tissue engineering applications including the regeneration of bone. This study explores the potential of the versatile ionic-complementary peptide, FEFEFKFK, for such a purpose as this peptide spontaneously self-assembles into β-sheet-rich fibres that subsequently self-associate to form self-supporting hydrogels. Via simple live/dead cell assays, we demonstrated that 3 wt% hydrogels were optimal for the support of osteoblast cells. We went on to show that these cells are not only viable within the three-dimensional hydrogel but they also proliferate and produce osteogenic key proteins, that is, they behave like in vivo bone cells, over the 14-day period explored here. The gel elasticity increased over time when cells were present – in comparison to a decrease in control samples – indicating the deposition of matrix throughout the peptide scaffold. Moreover, significant quantities of calcium phosphate were deposited. Collectively, these data demonstrate that ionic-complementary octapeptides offer a suitable three-dimensional environment for osteoblastic cell function.